Transcriptomic Validation of the Protective Effects of Aqueous Bark Extract of Terminalia arjuna (Roxb.) on Isoproterenol-Induced Cardiac Hypertrophy in Rats - Kumar, Gaurav; Saleem, Nikhat; Kumar, Santosh; Maulik, Subir K.; Ahmad, Sayeed; Sharma, Manish; Goswami, Shyamal K. (Frontiers in Pharmacology, 2019)
Aqueous extract of the bark of Terminalia arjuna (TA) is used by a large population in the Indian subcontinent for treating various cardiovascular conditions. Animal experiments have shown its anti-atherogenic, anti-hypertensive and anti-inflammatory effects. It has several bioactive ingredients with hemodynamic, ROS scavenging and anti-inflammatory properties. Earlier we have done limited proteomic and transcriptomic analysis to show its efficacy in ameliorating cardiac hypertrophy induced by isoproterenol (ISO) in rats. In the present study we have used high-throughput sequencing of the mRNA from control and treated rat heart to further establish its efficacy. Isoproterenol (5mg/kg/day s.c.) was administered in male adult rats for 14 days to induce cardiac hypertrophy. Standardized aqueous extract TA bark extract was administered orally. Total RNA were isolated from control, ISO, ISO + TA and TA treated rat hearts and subjected to high throughput sequence analysis. The modulations of the transcript levels were then subjected to bio-informatics analyses using established software. Treatment with ISO downregulated 1129 genes and upregulated 204 others. Pre-treatment with the TA bark extracts markedly restored that expression pattern with only 97 genes up-regulated and 85 genes down-regulated. The TA alone group had only 88 up-regulated and 26 down-regulated genes. The profile of expression in ISO+TA and TA alone groups closely matched with the control group. Total three hundred and sixteen unique genes were down-regulated by ISO, and their levels were restored upon TA treatment. The genes that were modulated included those involved in metabolism, activation of receptors and cell signalling; cardiovascular and other diseases. Networks associated with those genes included those involved in angiogenesis, extracellular matrix organization, integrin binding, inflammation, drug metabolism, redox metabolism, oxidative phosphorylation and organization of myofibril. Overlaying of the networks in ISO and ISO_TA group showed that those activated in ISO group were mostly absent in ISO_TA and TA group, suggesting a global effect of the TA extracts. This study for the first time reveals that TA partially or completely restores the gene regulatory network perturbed by ISO treatment in rat heart; signifying its efficacy in checking ISO-induced cardiac hypertrophy.